The position of the Entente States on the idea of Armenia’s independence (1917 and early 1918) - POGHOSYAN, Samvel; GHRMAJYAN, Genya (Historia i Świat, 2023)
The article highlights the emergence of the idea of Armenia’s independence at the end of the First World War. The Russian revolutions and the position of the United States brought new ideas to the problems of colonization and self-determination of nations. In the autumn of 1917, representatives of the great powers began to speak positively about the independence of Armenia. This eventually led to the declaration of independence of Armenia on May 28, 1918. The article is based on archival materials and collections of documents. Many archival sources are introduced into scientific circulation for the first time. The analyzes were presented based on verified facts. The study was conducted by the historicalcomparative method, according to the principle of historicity. An attempt has been made to present the problem in its entirety. In this article, we have revealed the position of Great Britain, France and the United States on the issue of the formation of an independent Armenian state.